KINERJA KANTOR IMIGRASI KELAS I PEKANBARU DALAM PENGAWASAN IMIGRAN ILEGAL DI KOTA PEKANBARU - Rosa Asmita Limbong; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Performance Class I Immigration Office Pekanbaru in Monitoring Illegal Migrants in Pekanbaru current public concern which has not been maximal performance of the immigration office in the supervision of illegal migrants viewed by phenomenas that exist, many of them are illegal migrants who roam the city of Pekanbaru, the number iillegal migrants is increasing and where to place illegal migrants close to the communities Pekanbaru causing problems for society Pekanbaru. Formulation of the problem in this research is how the performance of Class I Immigration Office Pekanbaru in Monitoring Illegal Migrants in Pekanbaru.The purpose of this research is to understand and analyze the performance of Class I Immigration Office Pekanbaru in Monitoring Illegal Migrants in the city of Pekanbaru and to analyze the factors that influence the performance of Class I Immigration Office Pekanbaru in Monitoring Illegal Migrants in the city of Pekanbaru. This research used Mahmudi theory with indicators: Inputs, Process, Outputs, Outcomes, Benefits and Impact.This research methods is using exploratory qualitative approach. Informants in this research are Member of Immigration Office, Member of Parliament Pekanbaru, and Illegal Migrants. Data collection techniques in this research are interviews, observation and documentation.The results of this research is the performance of Class I Immigration Office Pekanbaru in Monitoring Illegal migrants in the city of Pekanbaru less than maximum. This was evidenced by illegal immigrants still roam freely, the ineffectiveness of the rules, the presence of illegal migrants has been bringing negative impacts on society Pekanbaru. Factors affecting the performance of the immigration office of human resources, tasks, policies and language.Keywords: Organizational Performance and Monitoring.